FAULT FEATURE EXTRACTION OF VIRIABLE RORATION SPEED GEARBOX GEAR BASED ON VMD AND ORDER TRACKING - DIE XuPeng; KANG JianShe; CHI Kuo (Jixie qiangdu)
It is difficult to extract the fault features of gearbox gears under the condition of variable rotation speed,because of the order signals interfere with each other. To solve this problem,a fault feature extraction method for gearbox gears based on VMD（ Variational Mode Decomposition） and order tracking technology is proposed. The method resamples the vibration signal in angular domain by computed order tracking technology. After obtaining the resampled signal,it would be adaptively decomposed by VMD according to the different center order,and then select the fault signal fron the IMFs（ Intrinsic Mode Function） by kurtosis criterion. Finally,the fault signal is processed by the fast kurtogram,filter and squared envelope demodulation. Through the gear fault test and comparative analysis of gearbox at variable rotation speed,it shows that this method can effectively extract the gear fault characteristics of gearbox at variable rotation speed. It has obvious noise reduction effect and clear features,which is suitable for gear fault feature extraction of variable rotation speed gearbox.